Modified Cascaded H-Bridge Multilevel Inverter using Trinary DC source - Prashant Diwan, Anuja; Booma Nagarajan, N; Murugan, T; Ashrafudeen, S; J. Jenito Paul, G (International Journal of Engineering and Technology, 2018)
In this paper, single phase nine level cascaded multilevel inverter using trinary voltage source is described. Normally for getting nine level MLI output, four H-Bridges are required. But in proposed method, nine level output is achieved by using two H-Bridges only. Performance of Multilevel inverter is improved by using modular switching pattern. This method reduces the number of switches to the half and thus reduces switching losses. Since the number of levels at the output voltage is increased, Total Harmonic Distortion (THD) gets reduced significantly. This presents simple configuration is simple and can be controlled easily. MATLAB-SIMULINK is used to validate the results of proposed technic, simulation is carried out using. The proposed method has been exhaustively compared with classical cascaded H-Bridge topology.Â